Exploring the role of oral bacteria in oral cancer: a narrative review - Hassan Mivehchi; Aisan Eskandari-Yaghbastlo; Parnian Pour Bahrami; Anis Elhami; Farbod Faghihinia; Seyedeh Tabasom Nejati; Kimia Sadat Kazemi; Mohsen Nabi Afjadi (Discover Oncology)
Abstract A growing body of research indicates that a wide range of cancer types may correlate with human microbiome components. On the other hand, little is known about the potential contribution of the oral microbiota to oral cancer. However, some oral microbiome components can stimulate different tumorigenic processes associated with the development of cancer. In this line, two prevalent oral infections, Porphyromonas gingivalis, and Fusobacterium nucleatum can increase tumor growth. The microbiome can impact the course of the illness through direct interactions with the human body and major modifications to the toxicity and responsiveness to different kinds of cancer therapy. Recent research has demonstrated a relationship between specific phylogenetic groupings and the results of immunotherapy treatment for particular tumor types. Conversely, there has been a recent upsurge in interest in the possibility of using microbes to treat cancer. At the moment, some species, such as Salmonella typhimurium and Clostridium spp., are being explored as possible cancer treatment vectors. Thus, understanding these microbial interactions highlights the importance of maintaining a healthy oral microbiome in preventing oral cancers. From this perspective, this review will discuss the role of the microbiome on oral cancers and their possible application in oral cancer treatment/improvement.